English student book for Grade 1 - Anna Yeomans (Oxford university press, 2022)
This book is designed to support young learners in developing their English language skills. This edition features engaging content that aims to build vocabulary, comprehension, and language usage through a variety of interactive and age-appropriate activities. The book includes clear instructions, colorful illustrations, and structured lessons to foster a love for reading and language learning. It provides a balanced approach to developing reading, writing, and speaking skills, making it a valuable resource for Grade 1 students.
Keywords: Textbook